Case report: A study on the pathological diagnosis of oral fibrosarcoma in a giant panda - Xiong, Zongliang; Ling, Shanshan; Li, Caiwu; Deng, Linhua; He, Ming; Wang, Chengdong; Li, Desheng; Chen, Zhengli (Frontiers in Veterinary Science, 2025)
A female giant panda presented with a large, hard mass on the right cheek, which was investigated at the Dujiangyan Base of the China Conservation and Research Center for the Giant Panda with computed tomography (CT) scans and biopsy of the oral mass, as well as venous blood sampling. Hematological tests revealed elevated levels of the tumor marker CA724, along with infectious disease, anemia, hepatic damage, and renal failure. Imaging studies identified a soft tissue mass in the right cheek area. Macroscopic pathological changes, histopathological features, and immunohistochemical analysis were consistent with a low-grade malignant fibrosarcoma within the oral cavity, indicating malignant potential. This case represents the first report of an oral tumor in a giant panda, providing valuable data for future clinical diagnoses of neoplasms in this species.